The role of protected and unprotected forest remnants for mammal conservation in a megadiverse Neotropical hotspot - Magioli, Marcelo; Rios, Elaine; Benchimol, Maíra; Casanova, Diogo Cavenague; Ferreira, Aluane Silva; Rocha, Joedison; Melo, Fabiano Rodrigues de; Dias, Marcelino Pinto; Narezi, Gabriela; Crepaldi, Maria Otávia; Mendes, Lúcia Ângelo Machado; Nobre, Rodrigo de Almeida; et al. (Elsevier, 2021)
The Brazilian Atlantic Forest of Southern Bahia is a megadiverse region given its remarkable number of species and endemism. Despite being a priority region for biodiversity conservation, the role of protected and unprotected forest remnants for long-term species conservation is unknown. Here, we unveil the main patterns of occurrence and distribution of medium- and large-sized mammals in remnants of the Atlantic Forest of Southern Bahia, to generate subsidies for applied conservation strategies. We recorded mammals using camera-traps, active search, and/or line-transect surveys and complemented our species list with literature data. We thus obtained information on richness attributes, relative abundance, and biomass of mammal species per forest remnant, compared assemblages in protected and unprotected areas, and finally investigated both species-area and biomass-area relationships. From 72 forest remnants assessed, we recorded 45 mammal species, including 19 threatened locally. Protected areas were richer in species, especially concerning threatened ones, and concentrated most of the mammal biomass, which presented consistently low values for most areas. The positive and significant species-area and biomass-area relationships further corroborate these patterns since protected areas are larger in size. Despite the historic anthropogenic pressures, we conclude that Southern Bahia still harbors an expressive mammal diversity, with protected areas being critical to maintain most of the species' richness and biomass across the entire region. Nevertheless, small unprotected remnants (<100 ha) safeguard mammal species, including threatened ones, stressing their importance to maintain mammal assemblages in one of the most important hotpoints of the entire biome.
Keywords: Assemblage composition; Biomass; Patch size; Relative abundance; Species-area relationship; Threatened species